Mean stress effect and fatigue crack closure in material from old bridge erected in the late 19th century - Lesiuk, Grzegorz (2019)
The problem considered in this paper is the structural integrity of old materials from the 19th century by means of fatigue crack growth problem. The authors present an overview of the fatigue fracture properties of old puddle iron members extracted from long-term operated bridges located in France. The fracture properties and fatigue crack growth results for 19th-century puddle iron are presented and compared with typical Kinetic Fatigue Fracture Diagram (KFFD) constructing methods. The presented results for fatigue crack growth rate description under mode I using Kapplied approach and Keffective approach differs significantly using variable mean stress effect – R-ratio (0.05; 0.7). As it was demonstrated, the hysteresis loop analyses allow to obtain the estimated crack closure level. From the engineering point of view, there is a strong need for generalization of the KFFDs description using mean stress robust parameter involving local crack tip behavior for old puddle iron. Additionally, there are discussed the strengthening methods based on CFRP for this type of ancient materials in the light of the obtained numerical results for strengthened and non-strengthened puddle iron/steel specimens using CFRP patches using local approach.